Carbamoyl Phosphate Synthetase Subunit MoCpa2 Affects Development and Pathogenicity by Modulating Arginine Biosynthesis in Magnaporthe oryzae - Liu, Xinyu; Cai, Yongchao; Zhang, Xi; Zhang, Haifeng; Zheng, Xiaobo; Zhang, Zhengguang (Frontiers in Microbiology, 2016)
Arginine is a semi-essential amino acid that affects physiological and biochemical functions. The CPA2 gene in yeast encodes a large subunit of arginine-specific carbamoyl phosphate synthetase and is involved in arginine biosynthesis. Here, an ortholog of yeast CPA2 was identified in the rice blast fungus Magnaporthe oryzae, and was named MoCPA2. MoCpa2 is an 1180-amino acid protein which contains an ATP grasp domain and two CPSase domains. Targeted deletion of MoCPA2 supported its role in de novo arginine biosynthesis in M. oryzae as mutant phenotypes were complemented by arginine but not ornithine. The ΔMocpa2 mutant exhibited defects in asexual development and pathogenicity but not appressorium formation. Further examination revealed that the invasive hyphae of the ΔMocpa2 mutant were restricted mainly to the primary infected cells. In addition, the ΔMocpa2 mutant was unable to induce a plant defense response and had the ability to scavenge ROS during pathogen-plant interactions. Structure analysis revealed that the ATP grasp domain and each CPS domain were indispensable for the proper localization and full function of MoCpa2. In summary, our results indicate that MoCpa2 plays an important role in arginine biosynthesis, and affects growth, conidiogenesis, and pathogenicity. These results suggest that research into metabolism and processes that mediate amino acid synthesis are valuable for understanding M. oryzae pathogenesis.